Safety and efficacy of percutaneous coronary intervention versus coronary artery bypass graft in patients with STEMI and unprotected left main stem disease: A systematic review & meta-analysis - Talal Almas; Ahson Afzal; Hameeda Fatima; Sadia Yaqoob; Furqan Ahmad Jarullah; Zaeem Ahmed Abbasi; Anoosh Farooqui; Duaa Jaffar; Atiya Batool; Shayan Ahmed; Neha Sara Azmat; Fatima Afzal; et al. (International Journal of Cardiology: Heart & Vasculature, 2022)
Introduction: Owing to its large area of supply, left main coronary artery disease (LMCAD) has the highest mortality rate among coronary artery lesions, resulting in debate about its optimal revascularization technique. This meta-analysis compares percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) for the treatment of LMCAD. Method: MEDLINE, TRIP, and Cochrane Central databases were queried from their inception until 25 April 2021, to determine MACCE (major adverse cardiac and cardiovascular events), all-cause mortality, repeat revascularization, myocardial infarction (MI) and stroke rates post-revascularization for different follow-ups. 7 RCTs and 50 observational studies having 56,701 patients were included. A random-effects model was used with effect sizes calculated as odds ratios (odds ratio, OR). Results: In the short term (1 year), PCI had significantly higher repeat revascularizations (OR = 3.58, 95% CI 2.47–5.20; p < 0.00001), but lower strokes (OR = 0.55, 95% CI 0.38–0.81; p = 0.002). In the intermediate term (2–5 years), PCI had significantly higher rates of repeat revascularizations (OR = 3.47, 95% CI 2.72–4.44; p < 0.00001) and MI (OR = 1.39, 95% CI 1.17–1.64; p = 0.0002), but significantly lower strokes (OR = 0.54, 95% CI 0.42–0.70; p < 0.0001). PCI also had significantly higher repeat revascularizations (OR = 2.58, 95% CI 1.89–3.52; p < 0.00001) in the long term (≥5 years), while in the very long term (≥10 years), PCI had significantly lower all-cause mortalities (OR = 0.77, 95% CI 0.61–0.96; p = 0.02). Conclusion: PCI was safer than CABG for patients with stroke for most follow-ups, while CABG was associated with lower repeat revascularizations. However, further research is required to determine PCI’s safety over CABG for reducing post-surgery MI.